Online survey: best practice - Issa, Tomayess (IGI Global, 2012)
This chapter aims to demonstrate how the online survey tool was used during the PhD and postdoctoral research stages to evaluate and assess the New Participative Methodology for Developing Websites from the Marketing Perspective. After reviewing techniques from numerous disciplines for methodology integration, a new methodology was produced and an online survey to assess the methodology was completed by website industry participants and information systems professionals in Western Australia. A new online survey was developed on the basis of the PhD results and 210 Web developers and information technology professionals from Australia assessed the new methodology. This chapter will discuss three factors: the advantages and disadvantages of using an online survey in helping to facilitate high quality research and an overview of the functionality of the online survey tool(s) from a researcher’s point of view. Finally, a practical set of recommendations and endorsements is presented regarding the adoption of an online survey from the researcher’s standpoint.